Analisis Modifikasi Pembangkitan Kunci Rivest Code 2 Dengan Metode Belum-Micali Generator (BM-G) Untuk Meningkatkan Nilai Confusion Terhadap Record Data Login Pada Database - Chairun Nisa Lubis (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The login data record in the database is a table that stores a number of data related to the username and password. The information contained in the username and password data certainly cannot be accessed arbitrarily by others, because the data is confidential. The discussion that will be carried out in this research is to conduct an analysis of the Rivest Code 2 key generation which is then modified by combining the method of generating the Not-Micali Generator (BM-G) key. The results of the modification process for Rivest Code 2 key generation, then testing the Rivest Code 2 algorithm for activities to increase the value of confusion for data records in the database